Implementation Of The Me-Smile Application At Dharmais Cancer Hospital: An Implementation Research - Nugroho, Heru; Wisnu Handoyo (Sean Institute, 2024)
Healthcare facilities must monitor waste generation data daily so it can always be tracked as reference for medical waste management. Mostly, each Fasyankes has a scale to record their medical waste generation at their facilities, but this data’s only available within the Fasyankes. The medical waste generation data from Fasyankes still needs to be recapitulated for reporting so that it’s available for policymakers to support the medical waste management from Fasyankes. However, human error significantly affects the data when weighing, because the waste weighing is done twice: first during the disposal and transfer of medical waste from its source to Temporary Disposal Site, and second when the medical waste is collected by the third party who has permission and MoU with the healthcare facility, with different monitoring officers present during the disposal to the TPS and during the collection by the third party. The numerous complaints regarding this matter led the Ministry of Health to collaborate with United Nations Development Programme (UNDP) to develop an application named ME-SMILE in 2023. This application utilizes Internet of Things technology with sensors, microprocessors, and modules. Type of Research: Implementation Research with Research Design: case study, which falls under descriptive analysis research, namely research that is focused on a specific case to be observed and analyzed thoroughly and meticulously.With this research, it is hoped to share experiences and knowledge for the authors, especially in addressing the issues of implementing the Me-Smile application in healthcare facilities.